Beyond educational quality: Excellence and equity as key concepts for evaluating the Costa Rican Educational System - Picado Arce, Karol (2025)
This essay provides a conceptual and methodological framework based on educational evaluation as a scientific discipline, to operationalize the development and validation of a system of key educational indicators, whose monitoring allows the implementation and evaluation of actions, policies and programs, for the improvement of education in Costa Rica, with a particular focus on basic education, defined as primary and secondary education. At a conceptual level, this work argues for the need to shift the notion of educational quality towards the more clearly definable constructs, such as educational excellence and equity. At a methodological level, it proposes the CIPP (Context, Input, Process, Product) model as the basis for the design of the system of indicators, which should be generated with a participatory approach, gathering information and consulting with various educational stakeholders. Likewise, the system is expected to contribute to the dissemination for its use, to facilitate monitoring by public opinion, and to function as a tool for accountability.